Trace elements in end-stage renal disease. 1. Methodological aspects and the influence of water treatment and dialysis equipment - Zima, T; Tesar, V; Mestek, O; Nemecek, K (Blood purification, 1999)
For human beings trace elements are essential nutrients with a gamut of functions. They are for instance indispensable components of many enzymes, so they have some regulatory functions and they may affect immune reactions and free radical generation. Altered blood levels of different trace elements have been described in patients with advanced renal failure and especially in those treated by different kinds of renal replacement therapy. Altered renal function may result in impaired renal excretion of trace elements and their accumulation or depletion in the body. The dialysate concentrate and water used for preparing the dialysate may be an important source of the accumulation or depletion of trace elements in dialyzed patients. The gain or loss of trace elements during dialysis depends on the gradient between the ultrafiltrable fraction of a particular element in serum and its concentration in the dialysis fluid, and also on the type and permeability of the dialysis membrane. There are some methodological problems concerning the handling and storing of blood samples and measurement techniques leading to the rather inconsistent results of different studies concerning trace elements in renal disease. Geographical variations and environmental contamination of soil and water and different dietary habits may significantly influence trace elements in these patients. The abnormalities of trace elements are primarily the result of uremia, and they may be further modified and sometimes greatly exacerbated by the dialysis procedure.
Keywords: Kidney Failure, Chronic; chemické techniky analytické; Humans; hemodialyzační roztoky; Diet; Renal Dialysis; flebotomie; látky znečišťující půdu; Soil Pollutants; Hemodialysis Solutions; Artifacts; stopové prvky; dialýza ledvin; artefakty; lidé; difuze; chronické selhání ledvin; Diffusion; Phlebotomy; Chemistry Techniques, Analytical; dieta; Trace Elements; Water Pollutants, Chemical; chemické látky znečišťující vodu